REDESAIN HALTE BUS BSD LINK MELALUI KONSEP ECO-SHELTER - Putri , Shafira Aulia; Refranisa, Refranisa (Universitas Medan Area, 2024)
Bumi Serpong Damai (BSD) is an independent city in the Greater Jakarta area. The BSD developer, Sinarmas Land, has begun to operate mass transportation specifically for the BSD area in the form of Bus Rapid Transit (BRT). For the success of this project, supporting facilities are needed in the form of proper bus stops for bus users. The background of this research was the discovery of conditions that were not optimal functionally and the lack of comfort and safety at the BSD Link bus stop. The purpose of this study is to analyze the problems that exist at the bus stop and find development solutions by redesigning to overcome the conditions of the BSD Link bus stop. Redesign or redesign is an activity of designing and re-planning a design that aims to realign a design so that it can be more optimal. This study uses qualitative methods, collecting data through analysis and interpretation. Data collection was carried out by observing the research object, making comments at the BSD Link bus stop location, as well as collecting data from several literatures in the form of journals, books, and other written references concerning this research topic. This research applies the Eco-Shelter Concept and its shape reflects the buildings in the BSD area that carry the concept of sustainable building (Green Initiative), namely the Green Office Park building. This bus stop design is a design development that solves the problems in the previous bus stop design. This research resulted in design development in the form of improving the quality of safe and comfortable facilities and the application of the Eco-Shelter concept which refers to the green initiative program.